Stock Returns And Disagreement Among Sell-Side Analysts - Hobbs, Jeffrey; Kaufman, David L.; Lee, Hei-Wai; Singh, Vivek (Journal of Applied Business Research, 2018)
Asymmetric information, investor optimism, and unbiased prices hypotheses are the main hypotheses proposed for explaining how investors’ difference of opinion may impact stock returns. We use a new measure for divergence in investor beliefs among sell-side analysts to test these three hypotheses. Our initial findings are not supportive of either the asymmetric information or the investor optimism hypotheses. However, since these two hypotheses predict opposing effects of divergence in opinion on stock returns, the effects could neutralize their respective impacts on stock prices. Our further empirical analysis though suggests that this is not the case. The weight of the evidence presented suggests that within the sell-side, the difference of opinion does not impose a bias on future stock returns.
Keywords: Asymmetric Information; Difference of Opinion; Investor Optimism; Unbiased Prices